Social-demographic factors as predictors of tuberculosis patients non-compliance to treatment in Nigeria (2019)
Tuberculosis (TB) is a potential fatal contagious disease and is mainly an infection of the lungs. Pulmonary and extra pulmonary tuberculosis are the two kinds common in Nigeria with Pulmonary TB accounting for 80% of all cases. The Direct Observation strategy on Treatment of Tuberculosis (DOT) is an international adopted strategy to improve adherence among patients. In spite of this strategy, tuberculosis cases are on the increase in Nigeria. The study investigates Social-Demographic Factors Predicting Non-Compliance of Tuberculosis Patients to Treatment in Nigeria. The research design is ex-post-facto. Four research questions guide the study and participants are 250 patients and health workers. Two instruments: Tuberculosis Treatment Compliance Questionnaire (TTCQ,) r= 0.82 and Health Facility Records of TB Patients are used to collect data which is analysed using descriptive and inferential statistics at 0.05 level of significance. It is found out that irregular visit to treatment centers, patients' partial recovery and decision to discontinue treatment are the characteristics that highly affect TB patients' non-compliance to treatment. The patients' characteristics that mostly influence TB treatment compliance and contribute to the model are educational level (P -.539, p<.05) and attitude of health workers (V -.315, p<.05). It is recommended that government should ensure that TB treatment centers are located across health centers which are in close proximity to enhance patients’ regular visits and treatment compliance. Patients should develop positive attitude towards Completing their treatment to avoid relapse.